The Natural Radionuclide Activity and the Risk of Potential Radiation in Health Effect: A Study on Beach Sand in Madura, Bali, and Lombok - Yogi Priasetyono; Murdahayu Makmur; Wahyu Retno Prihatiningsih; Mohamad Nur Yahya; Deddy Irawan Permana Putra (Universitas Airlangga, 2021)
Introduction: Beach sand is one of the widely used aggregates in construction, especially in coastal areas. However, beach sand contains a hidden risk, namely radioactive hazards. This research will analyze the radioactive activity of nuclides 226Ra, 232Th, and 40K on beach sand and calculate the health risk potential in radiation exposure to the household. Methods: Beach sands sampling was carried out on Madura Island, Bali, and Lombok in 2016. All samples were ovensifted and then put into Marinelli to be chopped using high-purity germanium (HPGe) gamma-ray detectors for three days. Results and Discussion: The average of 226Ra, 232Th, and 40K radionuclide activity on the beach sand in Madura were respectively 31.46 Bq/kg, 40.12 Bq/kg, and 334.04 Bq/ kg; in Bali were 25.10 Bq/kg, 7.71 Bq/kg, and 165.15. Bq/kg; and in Lombok the amount is 25.88 Bq/kg, 8.25 Bq/kg and 171.99 Bq/kg. The calculation of the radium equivalent (Raeq) value on beach sand in Madura, Bali, and Lombok has the highest value of 132.72 Bq/kg, 54.06 Bq/kg, and 55.92 Bq/kg. The gamma index (I) in Madura, Bali, and Lombok was 1.02; 0.39; and 0.40. For the calculation of Hex and Hin in Madura, Bali, and Lombok, the highest were 0.38; 0.15; 0.15; and 0.48; 0.23; 0.24. Conclusion: The activity of the three types of natural radionuclides from the three regions is still below the threshold value. Analysis of potential health risks showed in the gamma index value (I) indicator, which exceeds the safe threshold in the Madura beach sand sample.